REPRESENTASI KERESAHAN GENERASI MUDA DALAM LAGU “KAMI KHAWATIR, KAWAN” KARYA HINDIA: ANALISIS SEMIOTIKA ROLAND BARTHES - Rendyta Bintang Hapsari; Ratna Setyarahajoe; Muhammad Fadeli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study analyzes the representation of youth anxiety in the song "Kami Khawatir, Kawan" ("We're Worried, Friend") by Hindia using Roland Barthes' semiotic approach. The study employs a descriptive qualitative method, collecting data through observation and documentation of the song lyrics and music video. The analysis is conducted through Barthes' three levels of signification: denotation, connotation, and myth. The results reveal that the song represents various forms of anxiety experienced by young people, including family conflict, emotional and financial pressure, the desire to escape from problems, mental instability, and the search for a safe space to find peace. At the mythological level, the song constructs a critique of modern social norms that demand young people to always be independent and resilient. This study concludes that the song functions not only as a musical work but also as a communication medium that represents the social and emotional reality of contemporary youth.